CULTIVATING KNOWLEDGE IN AI ERA: ESSENTIAL DIGITAL RESOURCES ANDTOOLS FOR AGRICULTURAL RESEARCHERS - N.P. RAVI KUMAR and M. SANDHYA (The Journal of Research, PJTSAU, 2026)
Agricultural research todayoperates within a digital knowledge environment that combines field experiments, remotesensing, genomics, socio-economic inquiry, scholarly literature, research data and collaborative networks. This article identifies themost significant digital resources available to agricultural researchers and presents them in an outline. It differentiates specializeddiscovery services such as CAB Abstracts, AGRICOLA, FAO AGRIS, and J-Gate Agricultural and Biological Sciences frommultidisciplinary citation databases, including Google Scholar, while also elaborating on the complementary role of the One NationOne Subscription initiative. The article examines the pathways to open science through the ICAR Open Access Policy, KrishiKosh,DOAJ, Dryad, Zenodo, AgriRxiv, and bioRxiv.It further describes the effective use of reference managers, researcher identifiers,collaboration profiles, field-data applications, MOOCs, and more. Mastery of this ecosystem may shorten the time required totransform reliable information into resilient agricultural solutions. The article concludes that while artificial intelligence can enhancesemantic discovery, screening, extraction, and data mining, researchers must retain control over the search process, logic, sourceverification, ethics, privacy, and understanding.